Implementasi Sistem Kelistrikan Tanpa Kedip Berbasis Keandalan pada Gedung Futsal Sumatera Utara - Urtat Batu Ajis Bulawolo; Muhammad Fadlan Siregar (Riau Jurnal Teknik Informatika, 2025)
The National Sports Week (PON) is one of the largest sporting events in Indonesia held every four years. Aceh and North Sumatra are the organizers of the XXI PON 2024. The implementation of PON in the North Sumatra region is a special concern by all parties. PT PLN (Persero) UP3 Medan Utara takes part in maintaining electricity stability during PON activities, UP3 Medan Utara conducts an electricity reliability system without blinking, namely by backing up the load, and to find out the number of load requirements that are supplied and know the function of each unit of electrical equipment used from the measurement of installed power in the building is 41,500 Watts, 400 kVA transformer, 40 kVA UPS, 100 kVA generator and 250 kVA UGB. From the results of measurements taken in getting the value of cable measurements R (I = 36.17 and F = 50.20 Hz), S (I = 15.22 and F = 50.21 Hz), T (I = 24.48 and F = 50.21 Hz) and N (I = 25.46 and F = 50.19 Hz).